Family development fund: an alternative mode to enforcement of maintenance orders towards sustainable families in Malaysia - Ibrahim, Kamilia; Mohd Zin, Najibah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Md Said, Muhamad Helmi (2017)
This paper examines the issues and models related to the proposal of the setting up of a Family Fund as an alternative mode to an effective enforcement of Maintenance orders. It is a known fact that neglected payment of maintenance due to weak enforcement procedure and lackluster family support system causes financial problems and social sufferings to the affected parties. This study, which adopts data compilation from scrutiny of cases, revealed that the recurrent phenomenon is primarily due to the defaulting party (men) not having the means and at times being recalcitrant. The defaulting party’s poor financial capacity found in most cases of failure to pay maintenance, endorses the need to create a Family Fund as a source of funding. It is noted that in Islam saving is encouraged to take care of the welfare of families. To articulate the idea of the proposed Family Fund the study examines various existing Fund Models in Malaysia and visited Morocco and Spain, which have such Funds for an insight in its models. The study concludes with the proposal of a Family Fund, which is hoped to be a solution to the economic woes of divorced families as well as financially assist towards the sustainability of families with or without divorce.